The developing recession in the United States - Wynne Godley (PSL Quarterly Review, 2012)
This article points out that the expansion of aggregate demand in the US during the nineties was structured in a highly unusual way. There was a progressive tightening of the fiscal stance, so growth had to be powered by a uniquely rapid growth of private expenditure in excess of disposable income. This process was intrinsically unsustainable because it required very heavy borrowing, which caused a rise to record levels in debt/income ratios. If aggregate demand is to grow at an adequate rate in the medium term, there will have to be a large further fiscal relaxation. Yet fiscal policy alone cannot solve the problem because there has been a growing deficit in the balance of payments which will have to be corrected at some stage. The implications for the rest of the world of continued recession in the US could be very serious.